The melanopsin-directed white noise electroretinogram (wnERG) - Adhikari, Prakash; Zele, Andrew J.; Cao, Dingcai; Kremers, Jan; Feigl, Beatrix (Vision research, 2019)
The white noise electroretinogram (wnERG) provides a measure of the impulse response function under conditions of retinal equilibrium; it is yet to be determined how the electrical response generated by melanopsin ganglion cell photoreception is expressed in the impulse response. To this end, we recorded the human wnERG to continuous temporal white noise (TWN) stimuli that were melanopsin-directed (rod and cone silent) or cone-directed (rod and melanopsin silent). The impulse response of the electroretinogram was derived by cross-correlating the TWN stimulus with the wnERG response. We observed that the LMS-cone directed wnERG contained the expected N1 wave (24.1 ± 2.4 ms; mean ± SEM) and P1 wave (49.7 ± 1.8 ms). Melanopsin-directed stimuli produced a unique wnERG with a slower negative deflection (Nm) at 62.9 ± 3.3 ms followed by a positive deflection (Pm) at 126.3 ± 5.1 ms. Additional experiments indicated this melanopsin-directed wnERG response was not due to cone intrusion. The Nm and NmPm amplitudes increased with illuminance (32,000–80,000 Td; no rod intrusion) and melanopsin contrast (10–36% Michelson contrast). As there are known pathways connecting melanopsin cells to the outer retina, we then measured the wnERG to combined melanopsin and cone-directed stimuli to quantify melanopsin interactions with cone signalling. With the combined stimuli, the N1P1 amplitudes were suppressed by 59%, which may be a result of a destructive interference between the positive (P1) and negative (Nm) waves generated by the cone and melanopsin pathways. We conclude that the human wnERG to melanopsin-directed stimuli may reflect the combined response of intra-retinal melanopsin pathways, independent of rod and cone photoreception.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Electroretinogram; Melanopsin; Silent substitution; White noise electroretinogram (wnERG)